Anomalous temperature dependent thermal conductivity of two-dimensional silicon carbide. (20th August 2019) - Islam, A S M Jannatul; Islam, Md Sherajul; Ferdous, Naim; Park, Jeongwon; Bhuiyan, A G; Hashimoto, Akihiro
Abstract: Recently, two-dimensional silicon carbide (2D-SiC) has attracted considerable interest due to its exotic electronic and optical properties. Here, we explore the thermal properties of 2D-SiC using reverse non-equilibrium molecular dynamics simulation. At room temperature, a thermal conductivity of ∼313 W mK −1 is obtained for 2D-SiC which is one order higher than that of silicene. Above room temperature, the thermal conductivity deviates the normal 1/ T law and shows an anomalous slowly decreasing behavior. To elucidate the variation of thermal conductivity, the phonon modes at different length and temperature are quantified using Fourier transform of the velocity auto-correlation of atoms. The calculated phonon density of states at high temperature shows a shrinking and softening of the peaks, which induces the anomaly in the thermal conductivity. On the other hand, quantum corrections are applied to avoid the freezing effects of phonon modes on the thermal conductivity at low temperature. In addition, the effect of potential on the thermal conductivity calculation is also studied by employing original and optimized Tersoff potentials. These findings provide a means for better understating as well as designing the efficient thermal management of 2D-SiC based electronics and optoelectronics in near future.